Economic Inequality and Masculinity–Femininity: The Prevailing Perceived Traits in Higher Unequal Contexts Are Masculine - Moreno-Bella, Eva; Willis, Guillermo B.; Moya, Miguel (Frontiers in Psychology, 2019)
Previous studies have shown that economic inequality influences psychological processes. In this article we argue that economic inequality also makes masculine attributes more prototypical. In Study 1 (N = 106), using an experimental design, we showed that individuals of a society are perceived as more masculine than feminine when there is higher inequality. The Study 2 (N = 75) experimentally shows that the upper social class is perceived mostly with masculine traits, and that effect is greater when there is a high economic inequality. The lower social class is more clearly perceived with feminine traits. These results contribute with information about the consequences of economic inequality for social perception.